The Effect of Biochar Levels on the Efficiency of Nitrogen Absorption and some Growth Traits of Wheat (Triticum aestivum .L ( - Raheem Alwan Halool Jassim; Mohammed A. Naser; Mustafa A. Manshoud; Hawraa Naeem Jalal (University of Thi-Qar Journal of agricultural research, 2024)
A field experiment was carried out at the second research station of the College of Agriculture , Al-Muthanna University in the agricultural season 2022/2023 to study the effect of adding biochar levels on the efficiency of nitrogen (N) absorption and some growth characteristics of the wheat crop. Biochar was added at four levels (0, 1.5, 2, 2.5) percentage (%) by volume to the soil before planting. Planting took place on 11/23/2022. An experiment was applied in a completely randomized block design (RCBD) with three replications. The means were compared according to the Least Significant Difference (LSD) test at the probability level of >= 0.05. The percentage of chlorophyll in the plant, the efficiency of nitrogen absorption at the flowering and harvesting stages, the height of the plant, the biological yield, and the concentration of nitrogen in the plant at the flowering and harvesting stages were studied. The results of the study showed that there were significant differences when adding biochar in plant height ( A3, 107.73 Cm ) and chlorophyll content in the leaves ( A2 , 48.80 spad and A1 , 48.15 spad ) , as all treatments were superior to the control treatment. There were significant differences for adding biochar in the amount of nitrogen in the plant at the flowering ( A3 , 395 kg ha-1 ) and harvesting stage ( A3 , 250 kg ha-1 ), as all treatments outperformed on the control treatment. The results also showed that there were significant differences for adding biochar in flag leaf area ( A2 ,71.62 cm2 and A3 , 70.26 cm2 ) and the efficiency of nitrogen absorption at the flowering ( A3 , 64.4 % ) and harvesting stage ( A3 , 50 % ).